Corbicula fluminea (Bivalvia: Corbiculidae): a possible second molluscan intermediate host of Echinostoma cinetorchis (Trematoda: Echinostomatidae) in Korea - Chung, Pyung-Rim (The Korean Society for Parasitology, 2001)
More than 1,500 clams of Corbicula fluminea, the most favorable food source of freshwater bivalves in Korea, were collected from 5 localities to examine cercarial and metacercarial infection with Echinostoma cinetorchis. Although 3 clams infected with suspicious E. cinetorchis metacercariae out of 200 specimens collected at Kangjin, Chollanam-do were detected, no cercarial and metacercarial infections with E. cinetorchis were observed in field-collected Corbicula specimens. In the susceptibility experiments with laboratory-reared clams, those infected with miracidia of E. cinetorchis did not release their cercariae up to 60 days after infection. To confirm the identity of second intermediate host of E. cinetorchis experimentally, a total of 30 clams were exposed to the cercariae from Segmentina hemisphaerula that had been infected with miracidia of E. cinetorchis. The clams were susceptible to cercariae of E. cinetorchis with an infection rate of 93.3%. Metacercariae from clams taken more than 7 days after cercarial exposure were fed to rats (S/D strain), and adult worms of E. cinetorchis, characterized by 37-38 collar spines on the head crown, were recovered from the ileocecal regions. This is the first report of C. fluminea as a possible second intermediate host of E. cinetorchis.